IMO’s Guidelines on Particular Sensitive Sea Areas toward the Protection of Underwater Cultural Heritage - Dhiana Puspitawati; Rangga Vandy Wardana (Media Iuris, 2022)
As an international organization established with the aim of improving maritime safety and security of international shipping, IMO sets up various guideline in assuring the establishment of international shipping. One of the those guidelines is the Guidelines for the Identification and designation of Particular Sensitive Areas (PSSAs). This article aims to analyse whether it is possible that the in situ of underwater cultural heritage can be included as PSSAs. This way would implied restrictions to international shipping in order to protect and preserve underwater cultural heritage. This research conducted through legal analyses of relevant legal documents. The method used in this paper is normative legal research with in-depth literature studies. This paper argued that while it is possible to include in situ location of underwater cultural heritage as PSSAs, however, conflicting interpretation between national and international law as well as disputes between States are imminent. Thus, IMO should play decisive role in properly co-ordinated and decide which marine areas requires restrictions in relation to the protection and preservation of underwater cultural heritage. The restrictions to international shipping with regard to the protection and preservation of underwater cultural heritage should not in any way prevent other legitimate uses of the sea as envisages under the 1982 Law of the Sea Convention (LOSC), especially on the freedom of navigation regimes. Thus co-operation and communication between IMO, other international organization and coastal State is crucial.